Digitalization of Institutional Communication in Islamic Education: Opportunities and Challenges in the Era of Society 5.0 - Hafiz, Abdul; Burhan; Ratna Sari Dewi; Rasya Ahmad Nizar; Leli Romdaniah; Syifa Mauliza (Rayah Al-Islam, 2025)
Digitalization of institutional communication is increasingly becoming an important aspect in improving the effectiveness and quality of education, including in Islamic education institutions. This research aims to examine how digital communication technology is changing the pattern of institutional communication in Islamic education, identifying potential benefits, as well as obstacles that must be overcome. Through a qualitative approach with a literature study method. The research found that digital platforms can improve connectivity between educators, learners and institutions, encourage collaborative learning and improve administrative efficiency. However, obstacles such as the digital literacy gap, infrastructure limitations, and the need for value-based digital content remain key challenges. The novelty of this research lies in its particular focus on the intersection between Islamic education and Society 5.0, as well as providing policy-relevant analysis, especially in designing adaptive communication strategies, educator training, and ethical frameworks in the utilization of digital technology.